REVITALISASI KAWASAN WISATA PANTAI TANJUNG TIHU DI KECAMATAN BONE PANTAI - Umar; Eka, Rahmawati; Salongi, Asmin (Universitas Bina Taruna Gorontalo, 2025)
This study examines the revitalization of coastal settlements and tourism in Tihu Village using qualitative-descriptive methods. Field surveys were conducted from April to May 2025 in Tihu Village, Bone Pantai Subdistrict, Bone Bolango Regency, Gorontalo, including data collection, interviews, observations, and field verification. The results indicate that Tihu Village has high tourism potential but faces serious issues: irregular building structures, environmental degradation, inadequate housing conditions, poor road infrastructure, and pollution caused by waste disposal into the sea, creating an unhealthy environment. Comprehensive revitalization is necessary to improve environmental quality, strengthen coastal community resilience, and promote local economic growth through tourism. The program includes infrastructure improvements, spatial planning, enhanced accessibility, coastal conservation, and community-based sustainable tourism development. Implementation is expected to create a well-planned, comfortable, and sustainable area while improving community well-being through the tourism sector.